2014
DOI: 10.1002/anie.201409868
|View full text |Cite
|
Sign up to set email alerts
|

SN2P2: A Neutral Five‐Membered Sulfur–Pnictogen(III) Ring

Abstract: The novel aromatic ring compound 2,4-diphospha-3,5-diaza-thiole (cyclo-SNPNP) was synthesized via flash pyrolysis of SP(N3)3 and characterized by IR spectroscopy and (15)N isotope labeling. Quantum chemical computations indicate its formation by head-to-tail dimerization of SNP and subsequent elimination of a sulfur atom from the highly unstable boatlike six-membered-ring compound cyclo-SNPSNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
7
0
2
Order By: Relevance
“…During the past three decades, researchers have sought other, all-inorganic, aromatic species. For example, N 2 S 3 2+ , 20 N 3 S 2 + , 21 and SN 2 P 2 , 22 which are isolobal to cyclo -P 5 – , have been identified; but N 2 S 3 2+ is not stable in solutions (N 2 S 3 2+ ), SN 2 P 2 is only stable when isolated in an Ar matrix, and only N 3 S 2 + has proven to be stable enough for isolation. Cyclo -N 5 – , the first-row congener of cyclo -P 5 – , has only been observed in the gas phase, where it can be formed via collision induced dissociation (CID) of a compound containing the N 5 unit 23 , 24 or its presence inferred via labeling studies of azide ion produced in the decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…During the past three decades, researchers have sought other, all-inorganic, aromatic species. For example, N 2 S 3 2+ , 20 N 3 S 2 + , 21 and SN 2 P 2 , 22 which are isolobal to cyclo -P 5 – , have been identified; but N 2 S 3 2+ is not stable in solutions (N 2 S 3 2+ ), SN 2 P 2 is only stable when isolated in an Ar matrix, and only N 3 S 2 + has proven to be stable enough for isolation. Cyclo -N 5 – , the first-row congener of cyclo -P 5 – , has only been observed in the gas phase, where it can be formed via collision induced dissociation (CID) of a compound containing the N 5 unit 23 , 24 or its presence inferred via labeling studies of azide ion produced in the decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Just recently,Zeng, Beckers,and co-workers prepared the neutral SN 2 P 2 heterocycle (7,Scheme 2) by flash pyrolysis of SP(N 3 ) 3 at 1000 Ka nd trapped the product in an argon matrix at 16 K. This product was characterized by IR spectroscopy with structural assignments facilitated by computational investigations,w hich also suggest that 7 is formed by the head-to-tail dimerization of gaseous SNP to cyclic [SNP] 2 ,followed by loss of sulfur. [16] Thei solobal analogue of [P 2 N 3 ] À , cyclo-[P 5 ] À ,h as been explored as aligand in transition-metal chemistry as it offers additional coordination sites in relation to the ubiquitous [C 5 H 5 ] À ion. Fore xample,S cheer and co-workers demonstrated that the hybrid sandwich complex [(h 5 -Cp*)Fe(h 5 -P 5 )] (Cp* = C 5 Me 5 )c ould further coordinate with copper(I) halides.T he resulting species adopt large (nanoscale) fullerene-like topologies and represent nice examples of selfassembly.…”
Section: Methodsmentioning
confidence: 99%
“…[14] This trithiadiazolium dication is not stable in solution and its formation in the solid state is driven by the high lattice energy of the 1:2 salts. [16] Thei solobal analogue of [P 2 N 3 ] À , cyclo-[P 5 ] À ,h as been explored as aligand in transition-metal chemistry as it offers additional coordination sites in relation to the ubiquitous [C 5 H 5 ] À ion. [15] Just recently,Zeng, Beckers,and co-workers prepared the neutral SN 2 P 2 heterocycle (7,Scheme 2) by flash pyrolysis of SP(N 3 ) 3 at 1000 Ka nd trapped the product in an argon matrix at 16 K. This product was characterized by IR spectroscopy with structural assignments facilitated by computational investigations,w hich also suggest that 7 is formed by the head-to-tail dimerization of gaseous SNP to cyclic [SNP] 2 ,followed by loss of sulfur.…”
Section: C Ationic Tetrazaphospholium Salts [Pn 4 R(mes*)][alcl 4 ](mentioning
confidence: 99%
“…Erst kürzlich präparierten Zeng und Beckers den neutralen SN 2 P 2 ‐Heterocyclus ( 7 , Schema ) durch Flash‐Pyrolyse von SP(N 3 ) 3 bei 1000 K und isolierten das Produkt in einer Argonmatrix bei 16 K. Dieses Ringsystem wurde durch IR‐Spektroskopie charakterisiert und die strukturelle Zuordnung durch computergestützte Studien ermöglicht. Die Untersuchungen ergaben ebenfalls, dass 7 durch Kopf‐zu‐Schwanz‐Dimerisierung von gasförmigen SNP zu cyclischem [SNP] 2 und den anschließenden Verlust von Schwefel gebildet wird 16…”
Section: Methodsunclassified